العامل النحوي في نظر المحدثين -تمام حسان أنموذجا- - داودي, انتصار; شريط, فيروز; التجاني, هاجر (جامعة الوادي - University of Eloued, 2023)
إن موضوع العامل النحوي كان موضوعا بارزا في الدراسات النحوية القديمة والحديثة. والعامل من العمل: المهنة والفعل، والجمع أعمال، عمل عملا، وأعمله غيره واستعمله، واعتمل الرجل عمل بنفسه، والاعتمال: افتعال من العمل، وأعمل فلان ذهنه في كذا وكذا دبره بفهمه... وفي الاصطلاح العامل ما أوجب كون آخر الكلمة على وجه مخصوص من الإعراب. وقد ربُطت نظرية العامل منذ القدم بالحركات الإعرابية، وكان من أهم شروط إقامة النظرية هو عدم جواز الفصل بين العامل ومعموله، وقد كانت هذه النظرية نظرية صافية لكن العلماء قد غالوا نوعا ما وشددوا وضيقوا بمسحتهم الفلسفية والمنطقية، كما أنها لم تكن محل استحسان من طرف جميع النحاة القدامى، بل نجد منهم من انتقدها وخالفها. فنجد أنها جاءت على ثلاث طروحات: القول بأن العامل هو لفظ في الجملة أو معنى من المعاني النحوية، القول بأن العامل النحوي هو للمتكلم نفسه، أو لأنّه هو الله. ونجد أيضا اختلافات نحوية وأول ما يتبادر إلى الذهن عند سماع الخلافات هو الخلاف والصراع القائم بين المدرستين البصرية والكوفية. ومن الملاحظ أن العلماء بسبب تمسكهم وتعصبهم للنظرية فإنهم حين يصطدمون بما يتعارض مع ما جاؤوا به فإنهم يميلون إلى التكلف والتمحل للخروج من مأزقهم. ونجد للنظرية مؤيدين أمثال: محمـد خير الحلواني ومصطفى بن حمزة. أما المعارضين فنجد: إبراهيم مصطفى ومحمـد عيد. وأبرز معارض هو تمام حسان الذي اقترح بديلا وهو نظرية القرائن والتي هي الدلالة اللفظية أو المعنوية التي تمحض المدلول وتصرفه إلى مراد منه، مع منع غيرها من الدخول، وتنقسم إلى لفظية ومعنوية. ترجمة الملخص: The subject of the grammatical factor was a prominent topic in ancient and modern grammatical studies. And the worker from the work is the profession, and the verb and the plural are the origins, the work of the clients and the origin of others and used it, and the man relied on his own work, and the reliance: fabricated from the work, and the work of so-and-so has his mind in such-and-such his house with his understanding. In the working term, what necessitates the fact that the last word has a specific form of syntax. The factor theory has been linked since ancient times with syntactic movements, and one of the most important conditions for establishing the theory was the impermissibility of separating the factor from its agent. The ancient grammarians, but we find some of them criticized and disagreed. You will find that it came in three propositions: saying that the factor is a word in the sentence or a grammatical meaning, saying that the grammatical factor is for the speaker himself, or because he is God. One is also grammatical differences and the first thing that comes to mind when hearing differences is disagreement And the conflict between the two schools of visual and Kufic. It is noticeable that scientists because of their adherence to and fanaticism to the theory, when they collide with what Contradicts what they came with, they tend to affect and pretend to get out of their predicament. We find supporters of the theory such as: Muhammad Khair Al-Halawani and Mustafa bin Hamza. As for the opponents, we find Ibrahim Mustafa and Muhammad eid. The most prominent opponent is Tammam Hassan, who proposed an alternative, which is the theory of clues, which is the verbal or moral signification that purifies the signified and directs it to what is intended from it, while preventing others from entering ,and is divided to verbal and moral.